Review of Cidariplura Butler, 1879 (Lepidoptera, Erebidae, Herminiinae). Part 1: the Cidariplura gladiata species complex - Wu, Shipher; Owada, Mamoru; Wang, Min (Zootaxa, 2019)
The generic type species Cidariplura gladiata Butler, 1879 and its allies of the genus Cidariplura Butler, 1879 are reviewed. In total, there are seven recognized species ranging from Japan, Korea, Taiwan, China, Vietnam; and we provide descriptions of three new species: C. nanling sp. nov., C. luding sp. nov., C. hbun sp. nov. The species C. shanmeii Wu & Owada, 2013 is re-described since the type series was the existence of specimens belonging to both C. shanmeii and C. hbun. Key to all belonging species is given.